2005
DOI: 10.1086/427283
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Weekly Dalbavancin Therapy for Catheter-Related Bloodstream Infection Caused by Gram-Positive Pathogens

Abstract: Dalbavancin thus appears to be an effective and well-tolerated treatment option for adult patients with CR-BSIs caused by CoNS and S. aureus, including MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
186
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(193 citation statements)
references
References 23 publications
2
186
1
4
Order By: Relevance
“…Case studies have described effective use of ceftaroline as a treatment option for daptomycinrefractory persistent MRSA bacteremia in patients with infectious endocarditis or osteomyelitis [164,165]. In several studies on catheter-associated BSI with gram-positive pathogens, the new lipoglycopeptide dalbavancin showed signifDer Anaesthesist icantly better outcomes than vancomycin in terms of clinical and microbiologic response rates [166,167]. The duration of therapy depends on the course of infection.…”
Section: Catheter-associated Infectionmentioning
confidence: 99%
“…Case studies have described effective use of ceftaroline as a treatment option for daptomycinrefractory persistent MRSA bacteremia in patients with infectious endocarditis or osteomyelitis [164,165]. In several studies on catheter-associated BSI with gram-positive pathogens, the new lipoglycopeptide dalbavancin showed signifDer Anaesthesist icantly better outcomes than vancomycin in terms of clinical and microbiologic response rates [166,167]. The duration of therapy depends on the course of infection.…”
Section: Catheter-associated Infectionmentioning
confidence: 99%
“…A phase II study compared dalbavancin (n = 33; 1000 mg loading dose on day 1 and 500 mg on day 8) with vancomycin (n = 34; 1000 mg every 12 h) for the treatment of catheter-related bloodstream infections [152] and concluded that dalbavancin was superior (clinical success rate: 87 vs. 50 %; microbiological success rate: 95.7 vs. 78.6 %). In both arms, success was higher when catheters were removed.…”
Section: Dalbavancinmentioning
confidence: 99%
“…Animal models of infection show excellent activity against MRSA or GISA endocarditis, penicillin-resistant Streptococcus pneumoniae 12 pneumonia or MRSA pouch infection, and septicemia due to Staphylococci, Streptococci or Enterococci. This antibiotic has been evaluated for catheterrelated bacteremia 72 and skin and soft tissue infections. 73 Dalbavancin was effective and well tolerated in adult patients with catheter-related bacteremia caused by coagulasenegative Staphylococci, MSSA and MRSA in a comparative trial with vancomycin.…”
Section: Dalbavancinmentioning
confidence: 99%